Exploring Factors Influencing Immunization Utilization in Nigeria—A Mixed Methods Study - Akwataghibe, Ngozi N.; Ogunsola, Elijah A.; Broerse, Jacqueline E. W.; Popoola, Oluwafemi A.; Agbo, Adanna I.; Dieleman, Marjolein A. (Frontiers in Public Health, 2019)
Background In 2005, Nigeria adopted the Reach Every Ward strategy to improve vaccination coverage for children, 0-23 months. By 2015, Ogun state had full coverage in 12 of its 20 local government areas but eight had pockets of unimmunized children, with the highest burden (37%) in Remo-North. This study aimed to identify factors in Remo-North influencing the use of immunization services, in order to inform intervention approaches to tackle barriers to immunization utilization. Methods We carried out a cross-sectional study using mixed methods including a survey of caregivers of 215 children, 25 semi-structured interviews with stakeholders involved in immunization service delivery and 16 focus group discussions with community men and women (n=98). Two wards (Ilara and Ipara) were purposively chosen for the study. Data was analysed using the SAGE Working Group Vaccine Hesitancy model. Results Only 56 children (32.6%) of the 172 children over 9 months of age had immunization cards available for inspection. Of these, 23 (59.6%) were fully immunized, noticeably higher in Ipara than Ilara. However, when immunization status was assessed by card and recall, 84.9% of the children were assessed as fully immunized. Caregivers in the more rural Ilara had less knowledge of vaccine schedules. The importance of all doses was recognized more by Ipara respondents (95.5%) than in Ilara (75.3%) (p<0.05). Community links to immunization and household decision-making patterns influenced immunization use in both wards. Migrants and those living in hard-to-reach areas were disadvantaged in both wards. Health service factors like absence of delivery services, shortage of health workers, unavailability of vaccines at scheduled times, and indirect costs of immunization contributed to low utilization. Conclusion Immunization utilization was influenced by interlinked community and health services issues. Intervention approaches should ensure that communities’ priorities are addressed, actors at both levels involved and strategies are adjusted to suit contexts.